Research on time–management skills of employees in the process of creating value for the customer. (1st January 2015) - Pluta, Anna; Wójcik, Grażyna Paulina
The purpose of this article is to find out whether time management skills can have an impact on creating value for the customer. The basis for the deliberations conducted in the article is an analysis of literature and the results of our own research regarding future Polish workers. The presented considerations and the results of the study indicate that time management skills can affect the chain of dependence that is shaping value. In order to provide value to the customer, organisations should not forget about the employees and the skills they possess, especially those related to the rational management of time. This article focuses mainly on Poland and Polish organisations; however issues discussed also apply to other nationalities.